1988
DOI: 10.1159/000150027
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Herpetic Ocular Disease by Immunotherapy with Monoclonal Antibodies to Herpes simplex Virus Glycoproteins

Abstract: In this paper we describe the ability of monoclonal antibodies to prevent herpetic stromal or interstitial keratitis following corneal infection in an outbred mouse model. Monoclonal antibodies recognizing antigenic determinants on glycoproteins B, C, D, and E of herpes simplex virus type 1 were injected intraperitoneally into CF-1 outbred mice 24 or 48 h following inoculation of the cornea with the RE strain of herpes simplex virus type 1. Passive, postexposure immunization with monoclonal antibodies had litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…We have argued previously that in non-immune animals the extensive centrifugal spread of virus back to the eye is likely to contribute significantly to the later development of severe ocular damage such as irreversible corneal opacity (Dyson et al, 1987). Hence in passively immunized mice the restricted spread of infection in the nervous system seems the most likely explanation for the absence of such damage, that we and other workers (Metcalf et al, 1987(Metcalf et al, , 1988Raizman & Foster, 1988;Foster et aL, 1988;Thompson et al, 1988;Lausch et al, 1989) have observed in such animals.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…We have argued previously that in non-immune animals the extensive centrifugal spread of virus back to the eye is likely to contribute significantly to the later development of severe ocular damage such as irreversible corneal opacity (Dyson et al, 1987). Hence in passively immunized mice the restricted spread of infection in the nervous system seems the most likely explanation for the absence of such damage, that we and other workers (Metcalf et al, 1987(Metcalf et al, , 1988Raizman & Foster, 1988;Foster et aL, 1988;Thompson et al, 1988;Lausch et al, 1989) have observed in such animals.…”
Section: Discussionmentioning
confidence: 49%
“…Detailed studies have been done to identify which monoclonal antibodies to viral glycoproteins (Metcalf et al, 1987(Metcalf et al, , 1988 and which subclasses oflgG (Raizman & Foster, 1988) are capable of conferring passive protection, but little is known of their site of action in vivo. We now report that passive immunization of mice before inoculation of the cornea with virus has no direct effect on replication of virus in the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MAb reactive with infected cells but not virus could promote recovery from HSV infection (35). With some exceptions (36) neutralizing activity of MAbs has been shown to be unrelated to their in vivo protection in animal models (35,(37)(38)(39)(40). When tested, protection correlated with ADCC function (35,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Murine IgG antibody to HSV-1 (murine immune IgG) was purified from sera of mice infected by flank scarification with HSV-1 NS and bled 2 to 3 weeks postinfection. Polyclonal rabbit anti-HSV-1 (Dako), UP575 anti-gE, UP1928 anti-gI, and NC-1 anti-VP5 and murine monoclonal antibody (MAb) Fd69 anti-gI have been previously described (3,12,22,31,40,56). Antiactin MAb C4 was obtained from MP Biomedicals, while rat anti-mouse Thy1.2 (PharMingen) was used as a neuronal cell marker.…”
Section: Methodsmentioning
confidence: 99%